CONVOLUTION NEURAL NETWORK (CNN) FOR VIDEO PROCESSING A SURVEY (International Journal of Food and Nutritional Sciences, 2022)
The past decade focused on Image Processing. Recently it is being found that many have shown their keen interest in Video Processing. Convolution Neural Network (CNN) showed extraordinary results in the field of image processing; now we wish to bring the same computation power in video processing too. This paper deals with the detailed study of CNN which is used for video processing. This research paper is expected to provide a review on how CNN is applicable for video processing. We also have discussed the architecture of CNN. This paper also highlights the different models of CNN present for the task of video processing and their functionality